Overtraining and the endocrine system -- Part 2: Review of the scientific studies - Platen, P. (2002)
This paper will discuss the phenomenon that, despite continuous or increased training, performance of an athlete is stagnant or even decreases without any obvious reason such as illness or injury. There is still no uniform term to describe this phenomenon. Part 1 of this review paper will give an overview of the differently used terms and definitions in this connection. Independent of whether monotonous exercise, too extensive training, or too intensive individual training are the external triggers of an overtraining syndrome, different assumptions exist concerning the internal effects on the athlete. Following this article, part 2 of the review analyzes the possible role of endocrine systems in connection with the problem of overtraining based on the available scientific studies.